Ancora sull’incerto mestiere del nascere e del diventare genitori: i casi di cui alle sentenze nn. 32 e 33 della Corte costituzionale (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article analyses the innovations that have emerged from the recent constitutional judgments nos. 32 and 33/2021 concerning parenthood of homosexuals. The arguments are set out in the broader context of the constitutional rulings on the law on medically assisted procreation (n. 40/2004) and the steps forward and the milestones set out in this respect are highlighted, distinguishing what the Court says about the best interests of children born in the context of heterologous fertilisation for women and surrogacy carried out abroad (because these practices are prohibited in Italy). The final part also examines the procedural technique used by the Court in this case, trying to understand the reasons for it.
Keywords: Constitutional Court; Heterologous fertilisation; Surrogacy; Parenthood of homosexuals; Procedural solutions